Ruolo del citrato nel metabolismo osseo - Giuseppe Vezzoli; Giulia Magni; Monica Avino; Teresa Arcidiacono (AboutScience Srl, 2020)
Citrate is an organic compound involved in tricarboxylic acid cycle, regulation of acid-base balance, lipid metabolism and bone formation. The 90% of body citrate is deposited in bone tissue and is released with calcium ions during bone resorption; therefore, bone resorption contributes to maintain normal plasma levels of citrate together with kidney excretion. The parallel release of citrate and calcium from bones decreases the possibility of calcium-phosphate precipitation in soft tissues, as citrate can bind calcium ions in organic fluids. Citrate may also take part to the bone formation as it sustains the correct mineralization of bone organic matrix: its molecule binds calcium ions at the surface of hydroxyapatite nanocrystals and maintains the correct spatial disposition of nanocrystals, thus, stabilizing the structure of bone lamellae and sustaining biomechanical characteristics of bone tissue. Multiple studies observed that citrate administration significantly increased areal and volumetric bone mineral density at different locations of 1-2% per year and improved bone resorption markers as well. Therefore, it has been hypothesised a therapeutic role of citrate in osteoporosis; however, this role has to be better clarified to understand its real anti-fracture effect.